Penerapan SIMDA Dan Pengaruhnya Terhadap Kepuasan Pengguna Jasa Informasi Akuntansi - Parmin Ishak (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
The purpose of this research to the amounts of the influence of the application of simda users against satisfaction accounting seen from the guidebook , software , his database system , located to organizations a device the regions in Kabupaten Boalemo with a population of a number of 43 people consisting of all financial operators OPD Boalemo with quantitative research methods have, as for data collection techniques to mensurvey research locations and use of the questionnaire was as the tools and in kevalidtan test data in application of sports use spss v.24 with the methods of multiple regression analyst .As for the result of the study them shows that the guidebook had a negative and insignificant against satisfaction accounting users , in contrast to the software which influence positive and significant impact on accounting users , but distinct again with a database that gives a positive influence and insignificant to users.